METHODS OF PASSIVE DIFFUSION FOR AMMONIA DETERMINATION IN OPEN FACILITIES FOR ANIMAL PRODUCTION - Sousa, F. C.; Tinôco, I. F. F.; Saraz, J. A. O.; Souza, C. F.; Paula, M. O.; Silva, A. L.; Coelho, D. J. R. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The aim of this study was to compare the two methods mentioned by passive diffusion may adapt more easily to facilities that work with natural ventilation for most of the time, based on results from existing surveys related to various characteristics of both studies methods. The Saraz is a new methodology that has been tested and optimized for operation on natural ventilation, and has shown a recovery efficiency of volatilization of ammonia greater than 80%. The "Ferm Tube" is the first flow and passive sampler, have been mainly used for determining the emission of NH3 in feedlot cattle. The two methods were compared in terms of requirements, such as cost, efficiency, applicability and usability in open facilities. Overall, in terms of natural ventilation Saraz the method was more appropriate than Ferm Tube. However, the choice between one or other method will depend on a number of conditions such as economic resources and availability of laboratory reagents, possible types of analysis to be performed, in addition to the desired precision and difficulty of operation.